Interaksi antara Regulasi Emosi dan Komunikasi Sosial pada Anak dengan Disabilitas Intelektual - Ladya Ghaisani Kurniawan; Aldila Dyas Nurfitri; Lucky Ade Sessiani (Journal of Health, Medical, and Psychological Studies, 2025)
This study explores the emotional and social communication patterns of children with intellectual disabilities (IDD) through a qualitative case study approach. Two participants a 13-year-old boy and a 7-year-old girl underwent psychological assessment, in-depth interviews, and behavioral observation at RSD K.R.M.T. Wongsonegoro Hospital in Semarang. Data were analyzed thematically to identify patterns of emotional regulation, verbal and nonverbal communication, and social adaptability. The findings reveal that both children exhibited deficits in expressive and receptive language, limited emotional regulation, and restricted social engagement. Emotional dysregulation manifested as impulsive behavior, tantrums, and difficulty expressing feelings verbally, while communicative patterns were marked by low initiation, echolalia, and reliance on nonverbal cues. Parental interaction styles and environmental factors, such as inconsistent caregiving and limited stimulation, further shaped these communication dynamics. The study highlights that emotional and social communication challenges in IDD are not solely rooted in cognitive impairment but are also influenced by relational and environmental contexts. These insights emphasize the need for integrative interventions combining emotional coaching, family engagement, and inclusive social experiences to enhance adaptive emotional and communicative functioning among children with intellectual disabilities.